Clinical Dilemma of Diabetic Ketoacidosis and COVID-19 Infection - Sapkota, P.; Chalise, S.; Shrestha, P. (Kathmandu University Medical Journal, 2021)
The COVID-19 Pneumonia with diabetic ketoacidosis is a dreadful health condition. Diabetic ketoacidosis is one of the severe metabolic complications and it can be precipitated by infection. We presented a case of 48 years female with no known comorbidities who presented with COVID-19 symptoms and with Diabetic Ketoacidosis. The case presented with elevated inflammatory markers, high anion gap metabolic acidosis with type I respiratory failure. During admission, the oxygen saturation had marked drop, later her improvement was steady followed by gradual tapering of the oxygenation. Marked improvement was noticed in the subsequent follow-up. COVID-19 infection can be precipitated by preexisting diabetes or newly diagnosed diabetes and the severity of COVID-19 infection is more pronounced in patients with diabetes mellitus, thus should be managed timely and accordingly. The scarce studies among the COVID-19 cases with diabetic ketoacidosis reflect the need for further studies for the availability of a wider range of information.